Tác động của đô thị hóa đến tình trạng nghèo: phân tích dữ liệu các tỉnh/thành Việt Nam giai đoạn 2016–2023 - Nguyễn, Huy; Trịnh Thanh, Nhân; Nguyễn Huy, Long; Nguyễn Nhật, Trường; Cao Trương Phúc, Hậu (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study provides novel empirical evidence of the impact of urbanization on poverty in Vietnam. Using a panel dataset from 63 provinces/cities from 2016 to 2023 and spatial regression models, the study found a significant relationship between urbanization and poverty. Urbanization not only directly affects poverty within a province’s administrative boundaries but also poverty in other provinces, known as the spillover effect. However, this spillover effect is mainly originates by adjacent provinces and gradually diminishes when the distance between provinces increases. The findings imply that establishing new urban areas in remote areas and enhancing regional connectivity will increase poverty reduction efficiency.